Regarding the teaching of the subject «Higher Mathematics» at technical universities - Kurbonaliev, Akmal; Sadritdinova, Zulfiya (MMIT Proceedings, 2024)
The work reflects innovative methods in teaching higher mathematics, their content. In particular, it provides historical data on mathematicians who made a huge contribution to the development of this science and their impact on the evolutionary process of mankind.